Analisis Pengaruh Kualitas Pelayanan, Harga, dan Brand Image Terhadap Kepuasan Konsumen Restoran Pizza Hut Cabang Jember - Tyas Kurniawati; Bambang Irawan; Adi Prasodjo (UPT Penerbitan Universitas Jember, 2019)
This study aims to knowing the influence of service quality, price, and brand image. This study is explanatory research. Population is all Pizza Hut customer Jember branch. The sampling method for this study was doing with nonprobability sampling with purposive sampling technique and it got 120 respondents. Data analysis method is multiple linear regression with confirmatory approach. The hypothesis of research is there was influenced service quality toward customer satisfaction, there was influenced price toward customer saisfaction., and there was influenced of brand image toward customer satisfaction on Pizza Hut Restaurant Jember Branch. The result of study showed up that service quality has influenced customer satisfaction. It indicates that given service by Pizza Hut Restaurant Jember branch according to the customer's hope, and the given service is enough satisfy. In order that, highly service quality will increase customer satisfaction. Price is not influenced customer satisfaction. It cause estimated price in receiving session and normally price is not same as decision from Pizza Hut Jember branch. Brand image is not influenced toward customer satisfaction. It cause brand image which Pizza Hut's got, it has not influenced to positive and negative direction. Keywords: Brand Image, Price, Customer Satisfaction, Service Quality.